EFEKTIVITAS PELAYANAN KESEHATAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI KOTA DENPASAR - Izky Ova, Ayu Sabrina; Sudarsana, Arka (PIRAMIDA; Vol 15 No 2 (2019): PIRAMIDA`- Jurnal Kependudukan dan Pengembangan Sumber Daya Manusia, 2019)
The purpose of this research is the first to know the effectiveness of BPJS Health program seen from input, process and output indicators; secondly to know the perception of the community of BPJS Health program users about the benefits felt by BPJS Health participants. This research uses two methods of data analysis. First by using descriptive statistics method to know the level of program effectiveness. Second, using non parametric statistical method with Mc Nemar method to know the benefits of BPJS Health program. The sample used in this research is 100 respondents. The result of analysis shows that the effectiveness level of BPJS Health program is seen from the input, process, and output indicators in Denpasar city is already effective. This is seen from the average score obtained from each input, process and output indicators. This is seen from the average score of answers obtained from the respondents, because all indicators above average 3. BPJS Health program also provides benefits to participants include reducing the cost for treatment, increasing the level of health, better service quality and access to health become easier.